Changes in the Montagu's Harrier Circus pygargus diet in Eastern Poland across decades promote insects and reptilians, but not birds and rodents. Issue 10 (29th March 2021) - Kitowski, Ignacy; Jakubas, Dariusz; Mirski, Paweł; Pitucha, Grzegorz; Markowska, Kornelia
Abstract: We investigated temporal changes in diet composition of the Montagu's Harrier Circus pygargus breeding in natural habitat (calcareous peat bog) in SE Poland. We characterized diet composition in a three‐year period (2007–2009), based on pellet analyses. We investigated whether diet composition was affected by years or stage of breeding. We compared diet of the studied population between 2000s and 1990s and with other populations. We found that the food of the studied population was dominated by insects and mammals (by number) and mammals and birds (by biomass). Biomass and abundance of main prey items differed between studied years because of different air temperatures. We found some interannual differences in contribution of some prey items including higher number of thermophilic prey (insects and amphibians) in warmer years. Comparison of pellet composition in the 1990s and 2000s revealed significant increase in the abundance of thermophilic prey (insects and reptiles) and decrease of mammals including Microtus voles and birds. Those changes may be linked to habitat changes in areas neighboring peat bogs and climate change‐induced changes in prey communities. The studied population was able to respond to changes in foraging habitats and prey composition by opportunistic foraging on easily available prey. The diet of the studied population is the most similar to the geographically closest populations foraging in similar habitats and characterized by high contribution of insects. Abstract : Comparison of pellet composition of Montagu's Harrier in the 2000s revealed inter‐annual differences in abundance (a) and biomass (b) of prey items. Samples collected in the warmest 2007 [characterized by a higher contribution of of thermophilic prey (insects and amphibians)] clustered in different positions than those collected in 2008 and 2009.